2016
DOI: 10.7324/jabb.2016.40505
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Mycelial Growth of Mushrooms on Different Yam-based Culture Media

Abstract: This study reports the potential application of yams as an efficient substrate for isolating mushrooms from the fruiting body. It seems that the utilization of yams as the medium for edible mushroom cultivation, i.e. a substitute for PDA, may increase the economic value of yams. Yams (Dioscorea sp.) belong to the starch-rich and energy-rich tubers, together with cassava, sweet potato, and potato. There is little utilization of yams in Thailand because yams grow wild and uncultivated and thus sufficient quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The isolation technique described in Tudses [48] was used to obtain cultures of the mushrooms on Potato Dextrose Agar (PDA) (Oxoid, UK). Small pieces (2×2 mm 2 ) of inner tissues were removed from the caps with sterile sharp blades and placed on PDA amended with chloramphenicol at 100 mg.L -1 to inhibit bacterial growth.…”
Section: Culturing Of Mushroommentioning
confidence: 99%
“…The isolation technique described in Tudses [48] was used to obtain cultures of the mushrooms on Potato Dextrose Agar (PDA) (Oxoid, UK). Small pieces (2×2 mm 2 ) of inner tissues were removed from the caps with sterile sharp blades and placed on PDA amended with chloramphenicol at 100 mg.L -1 to inhibit bacterial growth.…”
Section: Culturing Of Mushroommentioning
confidence: 99%
“…Sharma et al (2019) investigated the effect of various liquid nutrient media on the growth of four strains of V. volvacea and found that the highest values of mycelial growth were obtained in malt extract broth, potato dextrose broth and sweet potato dextrose broth. Previously, Tudses (2016) had reported the possibility of using sweet potato as a substitute for PDA in the cultivation of this fungus. On the other hand, Brinda et al (2021) found that V. volvacea also grows satisfactorily on solid medium (PDA) supplemented with peptone.…”
Section: Edible Mushrooms Biotechnology Edible Mushrooms Biotechnolog...mentioning
confidence: 99%
“…26 As most MMs are incapable of using external sucrose as a carbon (C) source, preferring glucose and/or fructose, 27 standard media such as PDA are likely to favour MM mycelium growth only, but no balanced nutrients, as found in their native materials. [28][29][30] Phlebopus portentosus was successfully cultured in a medium with a C:N ratio of 10:1 18 , unlike the optimum C:N ratio of 1:4 found for non-MM Pleurotus tuberregium, suggesting that conventional media for non-MM species may not be suitable for MM culture. However, no similar studies have been documented for miombo MM, particularly Amanita loosii, Cantharellus miomboensis and Cantharellus heinemannianus, which are popular foods among communities in southern Africa.…”
Section: Introductionmentioning
confidence: 99%